Processing Banana Peel Organic Waste in Tourism Areas as an Effort to Control Aquatic Environmental Pollution - Tuhumury, Novianty; Sahetapy, Jacqueline M F; Matakupan, Jolen; Rijoly, Stefanno M A (Sam Ratulangi University, 2024)
This study aims to analyze the weight of waste, recycling potential, and processing of banana peel organic waste into eco enzyme as an effort to control environmental pollution. The research was conducted in August-November 2023 in the Pasar Minggu Beach tourist area, Ambon City. The data collection method used direct observation in the field. Banana peel waste data was collected for 4 days, then weighed for further processing into eco enzyme for 3 months. Waste generation data and recycling potential were calculated using the formula set by the National Standardization Agency. The results showed that the weight of banana peel waste generated was 32.2 kg with 195 visitors. The average waste generation obtained was 0.17 or 0.2 kg/person/day, meaning that every visitor who comes to the tourist attractions produces 0.2 kg of banana peel waste. Banana waste that can be recycled is 30 kg and produces 112.5 l of ready-to-use eco enzyme solution. Processing banana peel organic waste into eco enzyme solution contributes ecologically and economically positively. Keywords: Banana peel; Eco enzyme; Organic waste; Tourism; Waste generation. Abstrak Penelitian ini bertujuan untuk menganalisis berat timbulan, potensi daur ulang, serta pengolahan sampah organik kulit pisang menjadi eco enzyme sebagai upaya pengendalian pencemaran lingkungan. Penelitian dilakukan pada Agustus–November 2023 di kawasan wisata Pantai Pasar Minggu, Kota Ambon. Metode pengambilan data menggunakan metode observasi langsung di lapangan. Pengambilan data sampah kulit pisang dilakukan selama 4 hari, kemudian ditimbang beratnya untuk selanjutnya diolah menjadi eco enzyme selama 3 bulan. Data timbulan sampah dan potensi daur ulang dihitung merujuk pada rumus yang ditetapkan oleh Badan Standarisasi Nasional. Hasil penelitian menunjukan berat sampah kulit pisang yang dihasilkan sebesar 32,2 kg dengan jumlah pengunjung sebanyak 195 orang. Rata-rata timbulan sampah yang diperoleh sebesar 0,17 atau 0,2 kg/org/hr, artinya setiap pengunjung yang datang ke tempat wisata menghasilkan sampah kulit pisang sebesar 0,2 kg. Sampah pisang yang dapat didaur ulang sebesar 30 kg dan menghasilkan larutan eco enzyme siap pakai sebanyak 112,5 l. Pengolahan sampah organik kulit pisang menjadi larutan eco enzyme berkontribusi positif baik secara ekologis maupun ekonomis. Kata Kunci: Kulit pisang; Eco enzyme; Sampah organik; Wisata, Timbulan sampah